Anticancer prospection of salicin, a historical origin of aspirin - Islam, Muhammad; Dantas, Rafael Caetano MagalhÃ£es (International Journal of Medicine, 2017)
Salicin (an alcoholic Î²-glucoside), the historical origin of aspirin. It is chemically related to aspirin and tastes bitter like quinine and evident for a number of important biological activities. The human bitter taste receptor TAS2R16 (hTAS2R16) responds to Î²-glucosides such as salicin. Thus, a modulator effect on this receptor may link to salicin-induced anticancer effect. Moreover, it may act by reducing oxidative stress and inflammatory reactions. Among a number of anticancer cellular and molecular mechanisms, salicin is evident to act through suppressing the angiogenic activity in cancer cells. Salicin may be one of the important anticancer drugs. However, the research on this willow plant derived compound is not sufficient, especially in the context of anticancer drug investigation.